Kedudukan Advokat dalam Penanganan Tindak Pidana Ringan secara Non-Litigasi dan Litigasi - Ayu Lestari Tambunan; Herlina Manullang (Jurnal Hukum Lex Generalis, 2025)
This study examines the position of advocates in handling minor criminal cases, whether pursued through litigation or non-litigation. Advocates in their duties to analyze, authority, and responsibility in providing legal assistance in minor criminal cases are often underestimated but still provide legal protection for those in need. That in non-litigation handling, advocates play a role as mediators, legal consultants, and facilitators of dispute resolution outside the court to reach a fair peace agreement for both parties. Meanwhile, in litigation, advocates have a position as legal counsel who represents and defends the interests of clients before the court, in accordance with the provisions of Law Number 18 of 2003 concerning Advocates and the Criminal Procedure Code (KUHAP). Thus, the position of advocates in minor criminal cases remains highly significant, both in peaceful resolution efforts and in the judicial process, in order to ensure the fulfillment of citizens' legal rights and the achievement of substantive justice.